Die be-tekening van konsepte in die opvoedkunde met verwysing na opvoeding as ‘vorming’ en die kind as ‘wordende mens’ - Henning, O. A. (Koers, 1992)
In this article the opinion of many educationists that education is to be regarded as a formative process’by which the child can be ‘shaped’ or 'moulded’ in an unrestricted and dominative fashion is highlighted. As an alternative, the concept of the 'normative disclosure’ of the personality structure of the child is suggested as it brings the true meaning of education to the fore. The variety of meanings conveyed by the mentioned concepts, which tend to cause confusion, is ascribed to the outcome of a diversity of paradigmatic and theoretical presuppositions as well as to the outcome of disparity regarding the cosmological, anthropological and epistemological basis of education that has given rise to divergent interpretations of concepts in different schools of philosophy and even among individuals in the same school of thought.